2015
DOI: 10.1021/acs.jpcc.5b03370
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Study of Oxygen Reduction in Dimethyl Sulfoxide (DMSO) Solution: A Fundamental Study for Development of the Lithium–Oxygen Battery

Abstract: To develop a lithium−oxygen (Li-O 2 ) battery with an extremely high specific energy, mechanisms for the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) on a flat gold electrode in the aprotic polar solvent of dimethyl sulfoxide (DMSO) has been systematically investigated by electrochemistry in combination with in situ UV−vis absorption spectroscopy, surface-enhanced Raman vibrational spectroscopy (SERS), and ex situ infrared spectroscopy. In the Li-free DMSO solution, O 2 is efficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
191
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(214 citation statements)
references
References 37 publications
20
191
3
Order By: Relevance
“…Replacing 18 O 2 with 16 O 2 was realized by 10 minute purging 16 O 2 through the Raman cell, during which the Au electrode potential was set to be 2.4 V. At the end of gas exchange, in situ SERS showed that Li 2 18 O 2 still dominates on Au as expected (Figure 2a,green curve). [22][23][24][25] Theintensity of the Li 2 16 O 2 band increases as af unction of discharging time,a nd one prominent feature is that prolonged discharging time (for example, > 5h)leads to the complete disappearance of the antecedently formed Li 2 18 O 2 and only Li 2 16 O 2 remains,i ndicating that the former has been replaced by the latter.T he displacement of Li 2 18 O 2 by Li 2 16 O 2 detected by surface-sensitive SERS technique suggests that the reactive sites of ORR are at the Au j Li 2 O 2 interface,which in return provides evidence that at the stage of sudden death ORR is limited by the electron transport instead of Li + and O 2 transport. After 1hdischarging at 2.0 V, aweak band at about 790 cm À1 ascribed to the formation of Li 2 16 O 2 was observed (Figure 2a, blue curve).…”
Section: Angewandte Chemiementioning
confidence: 90%
See 1 more Smart Citation
“…Replacing 18 O 2 with 16 O 2 was realized by 10 minute purging 16 O 2 through the Raman cell, during which the Au electrode potential was set to be 2.4 V. At the end of gas exchange, in situ SERS showed that Li 2 18 O 2 still dominates on Au as expected (Figure 2a,green curve). [22][23][24][25] Theintensity of the Li 2 16 O 2 band increases as af unction of discharging time,a nd one prominent feature is that prolonged discharging time (for example, > 5h)leads to the complete disappearance of the antecedently formed Li 2 18 O 2 and only Li 2 16 O 2 remains,i ndicating that the former has been replaced by the latter.T he displacement of Li 2 18 O 2 by Li 2 16 O 2 detected by surface-sensitive SERS technique suggests that the reactive sites of ORR are at the Au j Li 2 O 2 interface,which in return provides evidence that at the stage of sudden death ORR is limited by the electron transport instead of Li + and O 2 transport. After 1hdischarging at 2.0 V, aweak band at about 790 cm À1 ascribed to the formation of Li 2 16 O 2 was observed (Figure 2a, blue curve).…”
Section: Angewandte Chemiementioning
confidence: 90%
“…Avery recent in situ TEM work on the Li-O 2 battery containing liquid electrolyte by Kushima et al [20] showed that the discharging reaction occurred at the interface between electrolyte and the reaction product, whereas in charging,t he reactant was decomposed at the contact with the cathode,i ndicating that the Li + ion diffusivity/electronic conductivity is the limiting factor in discharging/charging,r espectively.H owever,t he above in situ SEM and TEM studies are conducted under electron beam radiation (potentially damaging Li 2 O 2 and inducing defects or parasitic reactions) and high charging potentials (> 6o r even 8V) [18,19] are applied to decompose Li 2 O 2 ,w hich are very different to the situation of typical Li-O 2 cells containing liquid electrolytes. [23][24][25] It has been reported that discharging current density plays ac ritical role in the formation of Li 2 O 2 ,t hat is,s olution/ surface formation of Li 2 O 2 can be achieved by low/high current densities. 3.8 nm) by discharging to the state of sudden death.…”
Section: Identifying Reactivesites and Transport Limitations Of Oxygementioning
confidence: 99%
“…This interpretation is also in good agreement with the results presented by Yu and Ye who have shown by means of UV/vis spectroscopy that parallel to peroxide also a significant amount of superoxide is formed and that the share increases as the electrode is deactivated. 37 RRDE-measurements in connection with potential step experiments also show that ring currents are observed irrespective to which potential the disc electrode is stepped, whereas the peak height of the ring current depends on the disc potential. 11 It is the prevailing view in literature that the species that reacts at the ring electrode is superoxide.…”
mentioning
confidence: 82%
“…Recently, based on UV/vis and SERS studies, Yu and Ye have proposed that the second peak is due to the oxidation of LiO 2 . 37 This reaction should come along with a z-value of only one. Based on the data presented in Figure 8B we have to reject this interpretation.…”
mentioning
confidence: 99%
“…In thef ramework of Pearson's hard-soft acid-base (HSAB) theory,t his effect can be explained by increased stability of the solvation shell around the Li + ions in high DN solvents. [10] ) This concept was further developedb yJ ohnson, [9] who reported that the Li + -solventi nteraction was considered as the main factor determining LiO 2 solubility.I tw as concludedt hat in high DN solvents, disproportionation of LiO 2 in solutiond ominated over surfacee lectrochemical processes.…”
Section: Introductionmentioning
confidence: 99%